Respuesta :
Hi there!
[tex](5 {x}^{2} - 5x + 1) + (2 {x}^{2} + 9 - 6)[/tex]
First we can subtract between the right parenthesis.
[tex](5 {x}^{2} - 5x + 1) + (2 {x}^{2} + 3)[/tex]
Now we can just remove the parenthesis, since they don't have a function in this situation.
[tex]5 {x}^{2} - 5x + 1 + 2 {x}^{2} + 3[/tex]
Next up is rearranging the expression in order to collect the terms later.
[tex]5 {x}^{2} + 2 {x}^{2} - 5x + 1 + 3[/tex]
And finally we can collect the terms.
[tex]7 {x}^{2} - 5x + 4[/tex]
~ Hope this helps you!
[tex](5 {x}^{2} - 5x + 1) + (2 {x}^{2} + 9 - 6)[/tex]
First we can subtract between the right parenthesis.
[tex](5 {x}^{2} - 5x + 1) + (2 {x}^{2} + 3)[/tex]
Now we can just remove the parenthesis, since they don't have a function in this situation.
[tex]5 {x}^{2} - 5x + 1 + 2 {x}^{2} + 3[/tex]
Next up is rearranging the expression in order to collect the terms later.
[tex]5 {x}^{2} + 2 {x}^{2} - 5x + 1 + 3[/tex]
And finally we can collect the terms.
[tex]7 {x}^{2} - 5x + 4[/tex]
~ Hope this helps you!
Hi there!
( 5x² - 5x + 1 ) + ( 2x² + 9 - 6 )
⇒ 5x² - 5x + 1 + 2x² + 9 - 6
⇒ 5x² + 2x² - 5x + 1 + 9 - 6
⇒ 7x² - 5x + 10 - 6
⇒ 7x² - 5x + 4
~ Hope it helps!
[tex] [/tex]
( 5x² - 5x + 1 ) + ( 2x² + 9 - 6 )
⇒ 5x² - 5x + 1 + 2x² + 9 - 6
⇒ 5x² + 2x² - 5x + 1 + 9 - 6
⇒ 7x² - 5x + 10 - 6
⇒ 7x² - 5x + 4
~ Hope it helps!
[tex] [/tex]